A novel fiber interlaced liposomal delivery of ursolic acid: Development, structural characterization, in vitro and in vivo bioavailability studies - Joby Jacob; Vedashree M. Sharma; T.V. Valsaraj; Heggar Venkataramana Sudeep; Kuppam Sundeep; Karempudi Venkatakrishna; Shyamprasad Kodimule (Next Research, 2026)

Sustained Release of Liposomal Caffeine Using Novel Natural Fiber Interlaced Liposomal Technology: Development and Structural Characterisation - Vedashree M. Sharma; T. V. Valsaraj; Heggar Venkataramana Sudeep; Shyamprasad Kodimule; Joby Jacob (Journal of Pharmaceutical Innovation, 2024)

Possibly pathogenic bacteria in aerosols and foams as a result of aeration remediation in a polluted urban waterway - Joby Jacob; Ingrid Veras; Olga Calderόn; Holly A. Porter-Morgan; Joshua Tan; Harry E. Aguilar; Willis T. Elkins; Veronica P. Martinez Castro; Vania Fulton; Wesam K. Yousri (Folia Microbiologica, 2024)
Newtown Creek is a tributary of the Hudson River Estuary. It has a legacy of both industrial pollution and sewage pollution and has been designated a Superfund site. To ameliorate the chronically low levels of dissolved oxygen detected in the Creek, the New York City Department of Environmental Protection has been installing aerators. The abundance of various bacteria in the aerosols, foams, and water, at two sites in the Creek, was studied before, during, and after the aeration process. Additionally, aerosols and dispersed foams created by the aeration process were sampled and cultured to determine what unique taxa of bacteria could be grown and identified. Taxa including Actinobacteria and Firmicutes were prevalent in cultures taken from aerosols, whereas Gammaproteobacteria were prevalent in cultures taken from foam. Campylobacteria was found to have a significant presence in both samples taken after the aerators were turned off. These taxa include potentially pathogenic bacteria and are therefore of particular concern.

Efficacy of mating disruption compared with chemical insecticides for controlling Tuta absoluta (Lepidoptera: Gelechiidae) in Kuwait - Mustapha F. A. Jallow; Abdelhafiz A. Dahab; Mohammed S. Albaho; Vimala Y. Devi; Joby Jacob; Omar Al-Saeed (Applied Entomology and Zoology, 2020)